The influence of household saving motives on the propensity to save and portfolio allocation decisions - Ahmad Mahdzan, Nurul Shahnaz (2010)
The objective of this study is to examine the motives that drive the propensity of households to save and households' portfolio allocation decisions. This interest has been spurred by the issue of low personal saving rates that has been observed across the globe over the past two decades. In addition, the perplexities concerning portfolio allocation choices despite rapid innovations of financial products warrants the need for further investigation on household's asset allocation decisions.